Plant-derived H7 VLP vaccine elicits protective immune response against H7N9 influenza virus in mice and ferrets. Issue 46 (17th November 2015) - Pillet, S.; Racine., T.; Nfon, C.; Di Lenardo, T.Z.; Babiuk, S.; Ward, B.J.; Kobinger, G.P.; Landry, N.
Highlights: Rapid production of a plant-derived H7 vaccine against pandemic H7N9. One dose of the adjuvanted H7 vaccine induced 100% protection against lethal challenge in mice. Two doses of the unadjuvanted H7 vaccine induced 100% protection against lethal challenge in mice. The adjuvanted H7 vaccine induces humoral and cell-mediated immune responses in ferrets. One dose of adjuvanted H7 vaccine reduced viral load in lungs and clinical signs in ferrets. Abstract: In March 2013, the Chinese Centre for Disease Control and Prevention confirmed the first reported case of human infection with an avian influenza A H7N9 virus. Infection with this virus often caused severe pneumonia and acute respiratory distress syndrome resulting in a case fatality rate >35%. The risk of pandemic highlighted, once again, the need for a more rapid and scalable vaccine response capability. Here, we describe the rapid (19 days) development of a plant-derived VLP vaccine based on the hemagglutinin sequence of influenza H7N9 A/Hangzhou/1/2013. The immunogenicity of the H7 VLP vaccine was assessed in mice and ferrets after one or two intramuscular dose(s) with and without adjuvant (alum or GLA-SE™). In ferrets, we also measured H7-specific cell-mediated immunity. The mice and ferrets were then challenged with H7N9 A/Anhui/1/2013 influenza virus. A single immunization with the adjuvanted vaccine elicited a strong humoral response and protected mice against an otherwise lethal challenge. Two doses of unadjuvanted vaccine significantly increased humoral response and resulted in 100% protection with significant reduction of clinical signs leading to nearly asymptomatic infections. In ferrets, a single immunization with the alum-adjuvanted H7 VLP vaccine induced strong humoral and CMI responses with antigen-specific activation of CD3 + T cells. Compared to animals injected with placebo, ferrets vaccinated with alum-adjuvanted vaccine displayed no weight loss during the challenge. Moreover, the vaccination significantly reduced the viral load in lungs and nasal washes 3 days after the infection. This candidate plant-made H7 vaccine therefore induced protective responses after either one adjuvanted or two unadjuvanted doses. Studies are currently ongoing to better characterize the immune response elicited by the plant-derived VLP vaccines. Regardless, these data are very promising for the rapid production of an immunogenic and protective vaccine against this potentially pandemic virus.